Physical exercise therapy for autism spectrum disorder: a scoping review of systematic reviews - Fei Fan; Ji Li; Xuan Zhang; Bo Wang; Zilin Chen; Yuchen Hu; Fei Han (Frontiers in Public Health, 2026)
Background Physical exercise therapy (PET) is used as a non-pharmacological intervention for individuals with autism spectrum disorder (ASD). However, the overall evidence landscape remains unclear. Methods This scoping review adhered to the Joanna Briggs Institute methodology and the PRISMA-ScR checklist. Searches were conducted in MEDLINE, EMBASE, Web of Science, and Cochrane Library from database inception to December 4, 2025. Included were systematic reviews that investigated PET for individuals with ASD. Two reviewers independently did data extraction and quality checks (AMSTAR-2). Results A total of 50 systematic reviews published between 2013 and 2025 were included. Ball sports/team sports, martial arts, mind–body exercises, aquatic therapy, and structured motor skill interventions were the most frequently studied modalities; the included reviews were generally of low methodological quality; most reviews reported improvements in motor skills, social communication, stereotyped behaviors, executive function, and sleep quality, but results were heterogeneous across outcomes; adverse events were rarely reported. Conclusion The available evidence suggests that PET may improve motor, social, behavioral, and sleep outcomes in individuals with ASD, though these findings are limited by low to critically low methodological quality, high heterogeneity, potential publication bias, and a lack of long-term follow-up. Systematic review registration The protocol is registered on OSF at DOI: 10.17605/OSF.IO/JVM4H ( https://osf.io/jvm4h ).